Insulin-Like Growth Factor-1 (IGF-1) Predicte the Diagnosis of Growth Hormone Deficincy in Short Prepubertal Children - Maan A. J. Bahrani; Ali A. Ali (College of Pharmacy University of Baghdad, 2017)
To study the serum IGF-1 level for prediction of growth hormone deficiency and its role in the diagnosis of short stature in children and adolescents. A  study was conducted on forty four (44) short children with growth hormone deficiency. Children were classified into Group I thirty five (35) prepubertal children and Group II (9) patients who entered puberty. In addition to forty (40) apparently healthy children as control group, also were divided into group I control(29) prepubertal &group II (11) pubertal  . IGF-1,GH ,Thyroid function ,serology for celiac disease , Hb level ,bone age  were done for all patients. IGF-1 and basal GH level (without provocative test) were done for control . There was a significant low difference between the serum IGF-1 level in the patients of group I in comparison to their serum level in control group I      {(90.98Â±23.69)  (121.83Â±23.69) (p<0.05)} . While there was no such  difference between the serum IGF-1 level in the patients of group II in comparison to their serum  level in control group II   {(184.59Â±196.52) (285.91Â±68.89) (p<0.05)}. This study shows that IGF-1 level is low compared to control in short GH deficient children who did not enter puberty, while it is less significant in children and adolescents who entered puberty. So IGF-1 is a suitable parameter to predict GH deficiency in short prepubertal children in whom GH deficiency was found by GH provocative testing. But this test is less reliable in children who entered puberty. Key Words:  IGF-1, Growth Hormone Deficiency, Short Stature.